Fracture mechanics of dental adhesives supplemented with Polymethyl-vinyl-ether-co-maleic anhydride. Issue 10 (19th May 2017) - Kim, Chris S.; Ozer, Fusun; Mante, Francis K.
Abstract: The objective of this study was to determine the effect of Polymethyl-vinyl-ether-co-maleic anhydride (PVM/MA), called Gantrez AN, on interfacial fracture toughness ( K IC ) of self-etch and etch-and-rinse dental adhesives. Sixty-five chevron-notched dentin-composite resin specimens were prepared. The following testing groups with different bonding agents were prepared and tested with a cross head speed of 0.1 mm/min: Clearfil SE (CF); Clearfil SE with Gantrez AN in primer (CFGp); Clearfil SE with Gantrez AN in bonding agent (CFG); Prime & Bond (PB); Prime & Bond with Gantrez AN (PBG). The K IC values were determined and compared. The mode of failure was examined with light microscopy. The mean K IC (standard deviation) of the Clearfil SE groups were 0.60 (0.09) MPa m 1/2 for CF, 0.64 (0.09) MPa m 1/2 for CFGp and 0.68 (0.16) MPa m 1/2 for CFG. The most common mode of fracture was cohesive. The mean K IC (standard deviation) of the Prime & Bond groups were 0.63 (0.09) MPa m 1/2 for PB and 0.41 (0.11) MPa m 1/2 for PBG. Adhesive fracture most commonly occurred in the Prime & Bond groups. Gantrez AN did not adversely affect K IC of the self-etch dental adhesive, but lowered K IC of the etch-and-rinse adhesive. Addition of Gantrez AN to self-etch adhesive (CF) may be warranted to produce an antibacterial effect. Clinical studies of bacterial attachment and anti-bacterial effects to further justify the use of Gantrez AN in bonding agents are warranted.